Modification of light-metal hydride properties for hydrogen-energy applications - Mohammad Ismail (University of Wollongong (Degree of Doctor of Philosophy), 2012)
Because it is a promising energy carrier, intensive efforts have been made to realize the potential of hydrogen to become a major energy carrier, for both mobile and stationary applications. Solid-state hydrogen storage has become an attractive option due to its high volumetric hydrogen capacity and favorable safety considerations. The purposes of this work are to enhancement the kinetics and tailor the thermodynamics of the light metal hydrides, LiAlH4 and MgH2, using different types of catalyst and the destabilization concept. In this study, a series of single metal hydrides such as NbFscatalyzed UAIH4 , SWCNTs-metal-catalyzed UAIH4 , Ti(>2 nanopowder-catalyzed UAIH4, and HfCU and FeCh-catalyzed MgHh; and a series of combined systems such as MgH2 -NaAlH4 and MgHh-LiAlFU have been systemically investigated for hydrogen storage.